The impact of monetary policy and exchange rate shocks in Poland: evidence from a time-varying VAR - Olga Arratibel; Henrike Michaelis (European Central Bank (ECB), 2014)
This paper follows the Bayesian time-varying VAR approach with stochastic volatility developed by Primiceri (2005), to analyse whether the reaction of output and prices to interest rate and exchange rate shocks has changed across time (1996-2012) in the Polish economy. The empirical findings show that: (1) output appears more responsive to an interest rate shock at the beginning of our sample. Since 2000, absorbing this shock has become less costly in terms of output, notwithstanding some reversal since the beginning of the global financial crisis. The exchange rate shock also has a time-varying effect on output. From 1996 to 2000, output seems to decline, whereas for periods between 2000 and 2008 it has a positive significant effect. (2) Consumer prices appear more responsive to an interest rate shock during the first half of our sample, when Poland experienced high inflation. The impact of an exchange rate shock on prices seems to slightly decrease across time.
Keywords: C30; E44; E52; F41; 330; Bayesian time-varying parameter VAR; exchange rate pass-through; monetary policy transmission